Helena Béjar, or the Progressive Potential of Philanthropy and Compassion - Cella, Paul (Daimon Revista Internacional de Filosofia, 2022)
From Karl Marx to current critics of 'effective altruism’, the elements of the political left demanding systemic change toward durable equity have long doubted the efficacy of private acts of charity in achieving progressive goals, including material equality or social justice. This article challenges this position, through an investigation of Spanish thinker Helena Béjar’s philosophical analyses of volunteer philanthropy and compassion as potentially conducive to progressive aims. It finally claims that Béjar illuminates new avenues of inquiry into existing questions, though her voice has been absent from relevant debates outside her native Spain, where one of her major works, The Bad Samaritan [El mal samaritano], was a finalist for the prestigious Anagrama Essay Prize. Desde Karl Marx hasta los actuales críticos del ‘altruismo efectivo’, los elementos de la izquierda política que reivindican cambios sistémicos orientados hacia una equidad duradera han dudado desde hace mucho de la eficacia de los actos privados de caridad para lograr objetivos progresistas, como la igualdad material o la justicia social. Este artículo cuestiona esta postura, mediante una investigación de los análisis filosóficos que la pensadora española Helena Béjar ha hecho de la filantropía voluntaria y la compasión, que ella considera potencialmente útiles para alcanzar fines progresistas. Finalmente, se afirma que Béjar ilumina nuevas vías de investigación sobre preguntas abiertas, aunque su voz no suene en los relevantes debates filosóficos fuera de España, donde una de sus grandes obras, El mal samaritano, fue finalista al prestigioso Premio nacional de ensayo Anagrama.